2020
DOI: 10.1155/2020/6149692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 27-Gauge and 25-Gauge Microincision Vitrectomy Surgery for the Treatment of Vitreoretinal Disease: A Systematic Review and Meta-Analysis

Abstract: Background. We performed a systematic review and meta-analysis to evaluate the safety and effectiveness of 27-gauge (27-G) microincision vitrectomy surgery (MIVS) compared with 25-guage (25-G) MIVS for the treatment of vitreoretinal disease. Methods. A systematic electronic search was conducted in March 2020 in PubMed, Embase, and the Cochrane library. Eligible criteria for including studies were controlled trials comparing 27-G vitrectomy with 25-G vitrectomy in patients with vitreoretinal disease. The main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 32 publications
1
22
2
Order By: Relevance
“…This was suggested also in a previous similar meta‐analysis study which showed similar promising outcomes for 27‐gauge microincision vitrectomy surgery in improving the best corrected visual acuity and reducing the wound closure time. 42 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different gender, ages, ethnicity, and other variants of subjects; since our meta‐analysis study could not answer whether different ages and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 97%
“…This was suggested also in a previous similar meta‐analysis study which showed similar promising outcomes for 27‐gauge microincision vitrectomy surgery in improving the best corrected visual acuity and reducing the wound closure time. 42 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different gender, ages, ethnicity, and other variants of subjects; since our meta‐analysis study could not answer whether different ages and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 97%
“…One meta-analysis of 940 eyes showed the mean operation time was significantly longer by 3 minutes for 27-G compared with 25-G vitrectomy. 13 As the instrument gauge decreases, more time may be needed for vitreous dissection. 14 In our study, average surgical time for pediatric cases was 53 minutes with a range of 20 minutes for cataract surgeries to 119 minutes for retinal detachments.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard of therapy for symptomatic ERM is a pars-plana vitrectomy with membranectomy and peeling of the inner limiting membrane (ILM peeling) [ 12 , 13 ]. However, this usually leads to cataract development in phakic eyes.…”
Section: Introductionmentioning
confidence: 99%